THE IMPACT OF ATMOSPHERIC AIR POLLUTION ON HUMAN HEALTH - Ikramova N. A.; Axmedova R. D. (The Conference Hub, 2025)
Nowadays, air pollution is considered one of the global environmental problems. The contribution of vehicles to pollution is a serious issue that is being discussed in every country. The amount of carbon dioxide (CO2), nitrogen oxides (NOx) and other harmful substances emitted by vehicles is increasing every year. According to the International Energy Agency (IEA), the transport sector accounts for about 24% of global greenhouse gas emissions.